An MCM-41-immobilized dichloro(pyridine-2-carboxylato)gold(iii) complex: an efficient and recyclable catalyst for the annulation of anthranils and ynamides. Issue 3 (3rd January 2023) - Xu, Zhaohui; Zeng, Jiajun; Cai, Mingzhong
Abstract : Heterogeneous gold(iii )-catalyzed annulation of anthranils and ynamides towards formylindoles using an MCM-41-anchored dichloro(pyridine-2-carboxylato)gold(iii ) complex [MCM-41-PicAuCl2 ] as a recyclable catalyst is described. Abstract : A new mesoporous MCM-41-immobilized dichloro(pyridine-2-carboxylato)gold(iii ) complex [MCM-41-PicAuCl2 ] was synthesized via an addition reaction of a dichloro(3-hydroxypyridine-2-carboxylato)gold(iii ) complex to triethoxy(3-isocyanatopropyl)silane, followed by immobilization on MCM-41 and was characterized by different physico-chemical techniques. In the presence of 5 mol% of MCM-41-PicAuCl2, the annulation reaction between anthranils and ynamides proceeded smoothly under mild conditions to afford diverse 6- or 5-formylindoles with high atom economy and good to excellent yields. This new heterogenized gold(iii ) complex can be easily recovered through a simple filtration process and recycled more than seven times without any apparent loss of its catalytic efficiency.